A Catastrophe Scenario Explanation for the Rise of Diapirs - DeJong, William; Mulder, Gea (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
According to current theory, the kilometers-high salt pillars ('diapirs') observed on many sites across the world are the product of a millions-year-long progressive process of cold flow of rock salt pushed upward by the overburden of soil covering it. This explanation is based on David Griggs' (1939) notion that plates of rock under high long-term stress behave like a fluid, have intrinsic viscosity, and can be represented using fluid dynamics equations. Griggs' idea has recently been falsified as a series of mistakes, each of which violating one or more principles of correct academic research, resulting in a gap in geological theory. The objective of this study is to fill that gap. We explain diapirs as salt lava pushed upward in kilometers of muddy, back-and-forth moving water, in a short period of time. This explanation necessitates the substitution of a catastrophe scenario for the known uniformitarian scenario for the evolution of the Earth's geological appearance. The catastrophe scenario we provide explains not only how diapirs form, but also how the Earth's key geological properties, such as waterflow-related geological macro-structures, originate. In contrast to the uniformitarian scenario, the catastrophe scenario's outcome is highly consistent with the actual geological and geophysical facts.